Animal Abuse in the Perspective of Positive Legal and Islamic Criminal Law - Inka Sahira; Maskur Rosyid (Walisongo Law Review (Walrev), 2022)
Massive cases of animal abuse occur and are left unchecked, requiring more attention. This article aims to analyze cases of dog abuse in the perspective of positive law in Indonesia and Islamic criminal law. This article is qualitative with a normative juridical legal research method and is presented descriptively. Field case data were obtained through interviews with dog lover’s communities, police, and former dog slaughterers in Yogyakarta. This article finds that the criminal act of molesting dogs at slaughterhouses in Yogyakarta has fulfilled the criminal element of violating Law no. 41 of 2014 concerning Amendments to Law No. 18 of 2009 concerning Livestock and Animal Health and Government Regulation no. 95 of 2012 concerning Veterinary Public Health and Animal Welfare. Mistreatment of dogs has fulfilled the elements of an act called jarīmah and is subject to ta'zīr whose punishment provisions are the authority of the government. So that according to both perspectives, animal abuse is a criminal act and deserves punishment. The omission of the case proves that the law is not implemented properly. This article recommends all parties to participate in guarding and monitoring the welfare and safety of animals from acts of abuse.Kasus penganiayaan hewan yang massif terjadi dan terbiarkan, membutuhkan perhatian lebih. Artikel ini bertujuan untuk mengalisis kasus penganiayaan anjing dalam perspektif hukum positif di Indonesia dan hukum pidana Islam. Artikel ini bersifat kualitatif dengan metode penelitian hukum yuridis normatif dan disajikan secara deskriptif. Data kasus lapangan didapatkan melalui wawancara dengan komunitas pecinta anjing, Polsek Pundong, dan mantan jagal anjing di Yogyakarta. Artikel ini menemukan bahwa tindak pidana penganiayaan anjing di rumah jagal di Yogyakarta telah memenuhi unsur pidana melanggar UU No. 41 Tahun 2014 tentang Perubahan Atas UU No. 18 Tahun 2009 tentang Peternakan dan Kesehatan Hewan dan PP No. 95 Tahun 2012 tentang Kesehatan Masyarakat Veteriner dan Kesejahteraan Hewan. Penganiayaan anjing telah memenuhi unsur-unsur suatu perbuatan disebut jarīmah dan dikenakan ta’zīr yang ketentuan hukumannya menjadi wewenang pemerintah. Sehingga menurut kedua perspektif, tindakan penganiayaan hewan merupakan tindakan pidana dan layak mendapatkan hukuman. Pembiaran kasus membuktikan bahwa hukum tidak terlaksana dengan baik. Artikel ini merekemondasikan kepada semua pihak untuk ikut serta mengawal dan mengawasi kesejahteraan dan keamanan hewan dari tindakan penganiayaan.